Project Based Learning: Pembuatan Motion Graphics “Affordable” untuk Klien LB LIA - Hidayat, Daffala Viro; Fami, Amata; Prayudo, Galih Ario; Mu'taz, Faris Afra (Lembaga Pengembangan Kinerja Dosen, 2024)
Project-Based Learning (PjBL) is a learning approach where students learn by actively participating in real projects or tasks. This approach aims to prepare learners to face real-world situations and develop skills relevant to careers and everyday life. The (PjBL) approach was used in the creation of this motion graphics titled